Mirror visual feedback training improves intermanual transfer in a sport-specific task: A comparison between different skill levels - Steinberg, F.; Pixa, N. H.; Doppelmayr, M. (Neural Plasticity, 2016)
Mirror training therapy is a promising tool to initiate neural plasticity and facilitate the recovery process of motor skills after diseases such as stroke or hemiparesis by improving the intermanual transfer of fine motor skills in healthy people as well as in patients. This study evaluated whether these augmented performance improvements by mirror visual feedback (MVF) could be used for learning a sport-specific skill and if the effects are modulated by skill level. A sample of 39 young, healthy, and experienced basketball and handball players and 41 novices performed a stationary basketball dribble task at a mirror box in a standing position and received either MVF or direct feedback. After four training days using only the right hand, performance of both hands improved from pre- to posttest measurements. Only the left hand (untrained) performance of the experienced participants receiving MVF was more pronounced than for the control group. This indicates that intermanual motor transfer can be improved by MVF in a sport-specific task. However, this effect cannot be generalized to motor learning per se since it is modulated by individuals` skill level, a factor that might be considered in mirror therapy research.